Plan de negocios para produccion y comercializacion de pulpa de nispero en el mercado de Machala - Suriaga Solano, Carlos Favian (2013)
This project develops the creation of a "Marketer of loquat pulp" in the city of Machala, El Oro Province, a business that is dedicated to the marketing of pulp. "PULPITA FABY" is aimed to attract more customers, especially consumers who are not satisfied in their dietary requirements concerning pulps, offering quality and variety in presentation, ie, consumers can find in different places variety fruit pulp according to your needs and especially in a hygienic environment and highly trained personnel."Pulpita Faby" will be located in the Pichincha streets between Junín and Juan Montalvo, downtown of the city of Machala. Local leased it fit with the machinery and tools necessary for the preservation of fruits, to offer a fresh product.Your target audience is middle class and upper middle of the city of Machala, consuming flesh, giving them confidence and delight food in the daily diet on informal occasions or social events. The price is a little higher than the competition, by the very fact of providing added value to the product, according to market research to target for this project which is intended , you agree to pay a higher price in exchange for receive quality and variety , fully satisfying their food needs to homes in the city of Machala.The distinctive value of this project was characterized by new facilities, tools, modern machinery. Having agreements for direct delivery to restaurants, grills, broilers, hotels. Attention seven days a week, Monday to Sunday and weekly discounts a type of fruit. Multikilos system for consumers that we prefer.The project is due to the need that exists today, in the city of Machala, of not having a local business that offers this type of business in a totally hygienic, variety in your fruit and especially product quality. It is true that there are supermarkets but are characterized by fresh pulp of day and range according to consumer need.The human resource that will be in charge will be the owner manager, the same to administer the business, two salesmen, a secretary - cashier, a driver and as ground staff did not have a counter.The total project cost is $ 49,700.00 funding will come from two sources: equity of $ 39,700.00 and $ 10,000.00 by a loan from the Cooperative "October 29" Ltd.The estimated net income for the first year of operation is $ 8,803.33 from the sale of pulp. The feasibility of the proposal is that the indicators such as NPV, IRR is positive. $ 4946.87 is obtained as net present value and internal rate 2.50% return which become attractive to investors. Just as you have calculated payback in 1 year, 1 month and 16 days.The social impact is would the image quality, service and attention that the firm provides to clients. With the implementation of this project is achieving nutritional development and Orenses Machaleños citizens with a quality product while providing employment opportunities between administrative and operational level. Environmental impact would not be so bad because it is a pulp processing plant, will have excellent containers for waste fruit when cut fruit to prevent odors and the attraction of rodents and insects (flies) that affect the food security of the people and the community.In the future the business will open branches within the city of Machala and the province of El Oro, as this possessed our brand in the minds of our customers, because in their market study will get good earnings in its first year of operation.